2021
DOI: 10.1111/jfbc.13652
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical characteristics of Asian sea bass bio‐calcium powders as affected by ultrasonication treatment and drying method

Abstract: Calcium is an important element that plays a critical role in bone growth and strength, as well as being responsible for the regulation of several cellular and tissue functions such as muscle contraction and exocytosis (Allen et al., 2006). Calcium-fortified products would be useful in improving calcium intake, especially for people with lactose intolerance who cannot consume milk or dairy products (Nemati

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 39 publications
(53 reference statements)
0
24
0
1
Order By: Relevance
“…Particle size and size distribution Particle sizes and size distribution of SCBC suspension were determined as detailed by Wijayanti et al (2021c). The suspension (10 mL) was mixed with DW (5 mL) and analysed using a laser particle size analyser (LPSA, LS 230, Beckman Coulter, CA, USA).…”
Section: Characterisation Of Scbcmentioning
confidence: 99%
“…Particle size and size distribution Particle sizes and size distribution of SCBC suspension were determined as detailed by Wijayanti et al (2021c). The suspension (10 mL) was mixed with DW (5 mL) and analysed using a laser particle size analyser (LPSA, LS 230, Beckman Coulter, CA, USA).…”
Section: Characterisation Of Scbcmentioning
confidence: 99%
“…Wijayanti et al . (2021) also documented that bio‐calcium from Asian sea bass ( Lates calcarifer ) backbone showed the major peak of 2θ (°) at 29.35°. This confirmed that cave‐B nest had higher crystallinity than house‐B nest , mainly related to the presence of calcium or calcite at higher level.…”
Section: Resultsmentioning
confidence: 94%
“…Linggawati (2016) documented that the XRD peak of cockle shells containing CaCO 3 exhibited high peak intensity of 2h (°) at 29.35°. Wijayanti et al (2021) also documented that bio-calcium from Asian sea bass (Lates calcarifer) backbone showed the major peak of 2h (°) at 29.35°. This confirmed that cave-B nest had higher crystallinity than house-B nest , mainly related to the presence of calcium or calcite at higher level.…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 90%
“…Ultrasonication can increase turbidity values by the suspension of microorganisms and small molecules that can be released as a result of the destruction of large molecules as a result of cavitation during sonication, and that the free radicals formed may come together with phenolic components and support the formation of water-insoluble polyphenols [52] , [50] , [184] .…”
Section: Ultrasonication Applications On Color Profile Of Foodsmentioning
confidence: 99%